2007
DOI: 10.1590/s1413-78522007000500011
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre diferentes métodos de avaliação funcional da marcha de ratos com lesão por esmagamento do nervo isquiático

Abstract: Foi realizado um estudo da correlação entre diferentes métodos de avaliação funcional do nervo ciático de ratos após lesão por esmagamento. Foram empregados no estudo 25 ratos da linhagem Wistar, de peso médio em torno de 250 g, submetidos a esmagamento controlado do nervo e avaliados por dois métodos convencionais para obtenção do índice funcional do ciático (IFC), baseados respectivamente na medida manual e computadorizada de parâmetros das impressões das pegadas dos animais, e por um novo método desenvolvid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 15 publications
1
10
0
10
Order By: Relevance
“…The difficulties observed then in the first weeks after production of the lesion gave rise to doubt regarding the fidelity of the method in this phase, which was what led us to investigate the reliability of the analysis method. 18 In our department, 12 the footprint capture method has recently evolved to obtainment by means of filming on a treadmill made in acrylic based on the studies of Varejão et al 13 These observations gave rise to the idea of building a treadmill with controlled speed equipped with a webcam connected directly to a portable computer allowing the filming of the animals' gait, and eliminating some variables observed in previous studies by our group. Speed control allows constant gait without the animal stopping, which could provide an untrustworthy measurement as the animal's weight could favor the In the first gait assessment the mean values of FSI were -2.7 (variation from -0.7625 to -4.5458) ± 1.2, and in the second assessment the mean values were -2.6 (variation from -0.0257 to -4.0693) ± 1.2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulties observed then in the first weeks after production of the lesion gave rise to doubt regarding the fidelity of the method in this phase, which was what led us to investigate the reliability of the analysis method. 18 In our department, 12 the footprint capture method has recently evolved to obtainment by means of filming on a treadmill made in acrylic based on the studies of Varejão et al 13 These observations gave rise to the idea of building a treadmill with controlled speed equipped with a webcam connected directly to a portable computer allowing the filming of the animals' gait, and eliminating some variables observed in previous studies by our group. Speed control allows constant gait without the animal stopping, which could provide an untrustworthy measurement as the animal's weight could favor the In the first gait assessment the mean values of FSI were -2.7 (variation from -0.7625 to -4.5458) ± 1.2, and in the second assessment the mean values were -2.6 (variation from -0.0257 to -4.0693) ± 1.2.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1st and 2nd weeks, the correlation index was close to zero, showing the low reproducibility of the method in this period, in which variability among the animals did not differ from variability among the examiners (p=0.24 and 0.32, respectively), due to the poor definition of the footprints. Gasparini et al 12 correlated different methods of functional gait assessment of rats with injury caused by crushing of rat sciatic nerve, the SFI (proposed by De Medinaceli) calculated in a manual and computerized manner (also proposed by De Medinaceli), the SFI calculated manually and with the filming method (proposed by Varejão) 13 and the computerized SFI with the filming method. The authors concluded that the analysis methods used guarantee the monitoring of functional recovery, but that the hypothesis of correlation of methods is real for the conditions in which the same mathematical formula is used, regardless of whether it is manual or computerized but, in the case there is combination among mathematical formulas and no correlation among methods, they also concluded that the method of evaluation through filming guarantees the monitoring of its regeneration in the first weeks, eliminating the difficulties existing in the traditional method of De Medinaceli, yet the authors did not control the walking speed of the animals.…”
Section: Functional Evaluation Of Nerve Regenerationmentioning
confidence: 99%
“…The right sciatic nerve was approached through a rectilinear longitudinal cutaneous incision on the lateral surface of the thigh and exposed all along its length, from the emergence underneath the gluteus maximus muscle up to its trifurcation at knee level. To produce the crush injury, we employed a portable deadweight device, [28][29][30] assembled with a load of 5,000 g. (Figure 1) With the nerve exposed, the animal was positioned in the device and the load was applied for 10 minutes, covering a segment measuring 5mm in length located 5mm below the nerve emergence point. 15,28 After production of the injury, the animal was removed from the crush device, the nerve was positioned in its anatomical bed and the surgical wound was sutured.…”
Section: Surgical Procedurementioning
confidence: 99%
“…As impressões foram registradas por uma câmera digital (Handycam -Digital Video Camera Recorder), tal como a utilizada por Gasparini et al 32 , fixada sob uma passarela de acrílico transparente com 43 cm de comprimento, 5,5 cm de altura e 8,7 cm de largura, tendo ao seu final uma casinhola de madeira. Os vídeos das pegadas foram digitalizados pelo programa Magix para obtenção das imagens das pegadas.…”
Section: Figura 1 Representação Esquemáticaunclassified
“…Em 1982, De Medinacelli et al 31 , tendo analisado a relação entre lesão no ciático e o apoio das patas na marcha, propuseram a utilização de um método de avaliação denominado índice funcional do ciático (IFC), baseado em mensurações nas patas traseiras de ratos. Gasparini et al 32 fizeram avaliação funcional da marcha de ratos com lesão por esmagamento do nervo isquiático pelo IFC, utilizando uma passarela de acrílico e registrando as pegadas por uma câmara digital. As imagens foram avaliadas por programa de computador para quantificar os parâmetros predeterminados por De Medinacelli et al 31 , modificados por Bain et al 33 .…”
Section: Introductionunclassified